Dynamics of the Vocal Fold Oscillation - Lucero, J.C. (Trends in Computational and Applied Mathematics, 2005)
This paper presents an analysis of the dynamics of the vocal fold oscillation at phonation, using low dimensional mathematical models. It shows that the wavelike motion of the vocal fold mucosa is responsible for a transfer energy from the air flow to the tissues, which fuels the oscillation. A hysteresis effect is present at the onset-offset of the oscillation, commonly observed as different laryngeal configurations at the start and end of phonation. This phenomenon may be modeled as a combination of a Hopf bifurcation of subcritical type and a cyclic fold bifurcation between limit cycles. Finally, the analysis shows that smaller larynges have more restricted oscillation conditions, because they are less capable of absorbing energy from the airflow, in agreement with experimental results from woman and child voices.